Surgical Excision of Fibrous Epulis in Generalized Periodontitis Stage III Grade C - I Komang Evan Wijaksana; Made Talitha Suryaningsih Pinatih (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2022)
Background: Fibrous epulis was the most frequent non-plaque-induced gingival lesions categories from biopsied cases included hyperplastic lesions, malignancies and benign neoplasms. Because the lesion is nonspecific and histology is the foundation of a more precise diagnosis, dentists may have difficulty identifying fibrous epulis from other disorders. Furthermore, the recurrence rate is significant, thus long-term follow-up is required for fibrous epulis after therapy. Purpose: to report the therapy of fibrous epulis and the follow up after eight months. Case: A 30-year-old nonsmoker healthy man presented with a 3-month history of an enlarging mass on the anterior left mandible gingiva. A clinical diagnosis was fibrous epulis in generalized periodontitis stage III grade C. Case Management: After evaluation of initial therapy, complete excision with a surgical blade and curettage of the lesion were planned for the lesion therapy. Histopathology finding confirm the prior clinical diagnosis of fibrous epulis. Eight months following surgery, the gingiva around the region had a healthy and desirable shape with no signs of recurrence. The patient's surgical recovery was good. Conclusion: Within the limitations of this case study, complete excision and curettage of the fibrous epulis lesion are the preferred treatments because of its high recurrence rate. The histopathologic examination is crucial for determining the final diagnosis, and long-term follow-up is essential.